Workshop Eksplorasi Masalah Numerasi dalam Konteks Kegiatan Berwisata di Kerinci - Putra, Aan; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Laswadi, Laswadi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This workshop aims to equip prospective mathematics teachers with the skills to explore numeracy problems in tourism contexts. The workshop is designed using a service learning approach and involves students from various universities across the Sumatra region. The core activities include identifying sequences of tourism activities, exploring numeracy problems embedded in each activity, and formulating context-based problems. The main output is a mini-project in the form of contextual open-ended math problems. The success of the workshop is measured through pretest and posttest comparisons, participant satisfaction surveys, and levels of active engagement. The results show that this approach effectively enhances students’ competence in designing mathematics instrumen based on local contexts.